Perfil transcricional ao longo do locus do Transcrito Específico do X inativo (XIST) na placenta de bovinos - Castro, Paloma Soares de (2020)
X chromosome inactivation (XCI) occurs as a way of compensating the imbalance between the homo and heterogametic sexes with respect to the gene expression. In mouse, it is established that the long non-coding RNA (lncRNA) X-inactive specific transcript (XIST) is essential to the iniciation of the XCI process. The most well-known antisense transcript in the mouse XIST locus is the TSIX, a negative modulator to XIST. However, in cattle these events are not yet totally established. Thus, the aim of this study was to characterize the patterns of strand-specific transcription along the XIST locus in the bovine foetal placenta. Total RNA was isolated from a female and male cotyledon samples using the PureLinkTM RNA Mini Purification Kit (Ambion, Austin, TX, USA). To detect strand-specific transcription, the cDNA was synthesized using forward and reverse primers specific for two regions of exon 1, exon 4 and exon 6 of XIST gene using the GoScriptTM Reverse Transcription System (Promega). As positive control, cDNA synthesized using Oligo(dT) and random primers was used. As negative control, it was performed a cDNA using Oligo(dT) and Random primers in the absence of the reverse transcriptase enzyme. Strand-Specific real-time PCR (SS-RT-PCR) analysis were run in a 7500 Fast RealTime PCR System (Applied Biosystems) using the SYBR Green PCR Master Mix (Applied Biosystems) and the same primer pairs that were used to synthesize cDNA. A análise da reação em cadeia da polimerase de transcrição reversa específica de cadeia (SS-RT-PCR) foi executada em um sistema 7500 Fast RealTime PCR (Applied Biosystems) usando o SYBR Green PCR Master Mix (Applied Biosystems) e os mesmos pares de primer que foram usados para sintetizar cDNA. Each cDNA sample (n= 10) was amplified and analyzed in duplicate and interpreted qualitatively, as presence or absence of expression. The three XIST isoforms (X1, X2, and X3) were identified, but only the X2 isoform covers all primers. The specificity of each amplicon was confirmed by the size of agarose gel (Exon 1 RepA – 139pb, exon 1 bXIST- 172bp, exon 4 TSIXM- 96pb, and exon 6TSIXU - 159bp) and by the melting curve and sequencing analysis. Sense transcription was detected throughout the XIST locus (exon 1, 4 and 6) for amplicons from male and female foetal cotyledons and antisense transcription only in exon 1 (RepA and bXIST) derived from female foetal cotyledon. Possibly the sense transcripts are the lncRNA XIST and that the antisense transcript expressed in exon 1 is not TSIX, but the XistAR homolog or other uncharacterized RNAs. The results show the importance of characterization as an aid to understand XCI in cattle. Also, it presents the relevance to take into account the possibility of antisense expression when it is proposed to perform gene expression studies, especially in non-coding RNA loci, where transcription from the two DNA strands is frequent.